Performance analysis on modified cycle of double absorption heat transformer with solution and coolant heat regeneration. (5th September 2016) - Ji, Guangju; Chen, Yaping; Wu, Jiafeng; Ji, Ge
Highlights: Double absorption heat transformer of solution and coolant regeneration was studied. New cycle has wider operating temperature range and higher COP and exergy efficiency. Average COP of new cycle is 6.2–9.1% and 3–3.6% higher than that of two old ones. Absorption-evaporation temperature t AE is an operation parameter to be optimized. Optimal t AE is related to waste heat, cooling water and supplying heat temperatures. Abstract: A modified cycle of double absorption heat transformer with heat regeneration of both solution and coolant is proposed by adding a heat exchanger at the inlet of coolant and outlet of dilute solution of the absorber-evaporator. The performances of three cycle schemes of double absorption heat transformers without regeneration, with solution heat regeneration and with both solution and coolant heat regeneration for absorber-evaporator are calculated and compared. The results show that the double absorption heat transformer with both solution and coolant heat regeneration has a wider operating range of absorption-evaporation temperature and higher coefficient of performance ( COP ) and exergy efficiency. When the temperatures of absorption, generation, condensation and absorption-evaporation are respectively 120–150 °C, 70 °C, 25 °C and 80–115 °C, the average values of COP or exergy efficiency of the new cycle is 8–9% and 2.5–3.5% respectively higher than the ones without heat regeneration and with solution heat regeneration only. The variation trends of COP and exergy efficiency of three cycles versus the temperatures of absorption-evaporation, condensation, generation and absorption are also presented. The impacts of absorption-evaporation temperature on COP and exergy efficiency under different temperature combinations of generation, absorption and condensation are presented for optimal design of the new double absorption heat transformers.